Analysis of urban heat islands with landsat satellite images and GIS in Kuala Lumpur Metropolitan City - Kasniza Jumari N.A.S.; Ahmed A.N.; Huang Y.F.; Ng J.L.; Koo C.H.; Chong K.L.; Sherif M.; Elshafie A. (Elsevier Ltd, 2024)
Cities are growing geographically in response to the enormous increase in urban population